The pope's dilemma : Pius XII faces atrocities and genocide in the Second World War - Kornberg, Jacques, 1933- (Toronto : University of Toronto Press, 2015)
A meticulous and careful analysis of the career of the twentieth century's most controversial pope, The Pope's Dilemma argues that Pius XII's refusal to condemn Nazi Germany and its allies was driven by the desire to keep Catholics within the Church.
Includes bibliographical references and index.
Print version record.
Master record variable field(s) change: 072
Keywords: Pius -- XII, -- Pope, -- 1876-1958.; Pius -- XII, -- Pope, -- 1876-1958.; World War, 1939-1945 -- Religious aspects -- Catholic Church; World War, 1939-1945 -- Atrocities; Holocaust, Jewish (1939-1945); RELIGION -- Christianity -- Catholic; Atrocities; HISTORY / Europe / Germany; 1939-1945; Electronic books